2020
DOI: 10.1055/s-0040-1708846
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-to-Tumor Metastasis of Multiple Meningiomas and Clear Cell Renal Cell Carcinoma Metastasis as First Clinical Appearance of Kidney Cancer: A Case Report and Analysis

Abstract: Background Meningioma accounts for more than 35% of all diagnosed brain tumors of the central nervous system and, moreover, it is the most common benign recipient of tumor-to-tumor metastasis. Several cases with tumor-to-meningioma metastasis by breast, lung, and intestinal cancer have been described before. Case description The case of a patient with a longstanding history of multiple meningiomas (n = 4) that suddenly became symptomatic and progressive in size is presented. Following extirpation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Since then, many other tumor-derived factors, including cytokines, chemokines, extracellular matrix components, small noncoding RNAs and tumor-shed extracellular vesicles have been shown to act as systemic signals that trigger the formation of premetastastic niches in lung, liver or lymph nodes in different preclinical models (149,261). Clinical evidence for the existence of premetastatic tissues comes from patients with meningioma (a benign brain tumor) who later progress with tumor-to-meningioma metastasis of breast, lung or renal cancer (88,264,270). It is suggested that the presence of pro-inflammatory macrophages and the high microvascular density in meningioma contribute to metastasis formation (88).…”
Section: A Preparing the Soil -The Concept Of The Premetastatic Nichementioning
confidence: 99%
See 1 more Smart Citation
“…Since then, many other tumor-derived factors, including cytokines, chemokines, extracellular matrix components, small noncoding RNAs and tumor-shed extracellular vesicles have been shown to act as systemic signals that trigger the formation of premetastastic niches in lung, liver or lymph nodes in different preclinical models (149,261). Clinical evidence for the existence of premetastatic tissues comes from patients with meningioma (a benign brain tumor) who later progress with tumor-to-meningioma metastasis of breast, lung or renal cancer (88,264,270). It is suggested that the presence of pro-inflammatory macrophages and the high microvascular density in meningioma contribute to metastasis formation (88).…”
Section: A Preparing the Soil -The Concept Of The Premetastatic Nichementioning
confidence: 99%
“…Clinical evidence for the existence of premetastatic tissues comes from patients with meningioma (a benign brain tumor) who later progress with tumor-to-meningioma metastasis of breast, lung or renal cancer (88,264,270). It is suggested that the presence of pro-inflammatory macrophages and the high microvascular density in meningioma contribute to metastasis formation (88). Similarly, the existence of a premetastatic tissue in sentinel lymph nodes resected from patients with solid tumors has been reported (302).…”
Section: A Preparing the Soil -The Concept Of The Premetastatic Nichementioning
confidence: 99%
“…Some studies have reported that perfusion MRI and magnetic resonance spectroscopy might be helpful in diagnosing TTM and differentiating it from a meningioma [ 19 20 ]. Dietterle et al [ 21 ] reported that a malignant tumor or TTM should be suspected in a tumor in a patient who has been symptom-free for many years if it suddenly increases in size along with neurological deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unknown how RCC may instead donate the "seeds" in a given case of TTM because there are very few cases published in the literature. Most cases with RCC as a donor in TTM involve intracranial, thyroid, and pulmonary neoplasms as recipients, in which most are benign neoplasms 5,10,[18][19][20][21][22] . An article in which RCC metastasized to a benign hemangioblastoma proposed that since benign tumors grow slowly and are often unnoticed for long periods, they are more likely to be involved by a more aggressive tumor in TTM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…They are also rarely involved in cases of TTM 16,17 . As the most fre-quent recipient tumor in TTM, it is uncommon for RCC to be a donor tumor; however, it has been reported to occur in TTM of intracranial, lung, and thyroid neoplasms 5,10,[18][19][20][21][22] . This case is the first to the best of our knowledge of an RCC being the "donor" to a lipoma in a case of TTM.…”
mentioning
confidence: 99%